Observing the restriction of another person: vicarious reactance and the role of self-construal and culture - Sittenthaler, Sandra; Traut-Mattausch, Eva; Jonas, Eva (Frontiers in Psychology, 2015)
Psychological reactance occurs in response to threats posed to perceived behavioral freedoms. Research has shown that people can also experience vicarious reactance. They feel restricted in their own freedom even though they are not personally involved in the restriction but only witness the situation. The phenomenon of vicarious reactance is especially interesting when considered in a cross-cultural context because the cultural specific self-construal plays a crucial role in understanding people’s response to self- and vicariously experienced restrictions. Previous studies and our pilot study (N = 197) could show that people with a collectivistic cultural background show higher vicarious reactance compared to people with an individualistic cultural background. But does it matter whether people experience the vicarious restriction for an in-group or an out-group member? Differentiating vicarious-in-group and vicarious-out-group restrictions, Study 1 (N = 159) suggests that people with a more interdependent self-construal show stronger vicarious reactance only with regard to in-group restrictions but not with regard to out-group restrictions. In contrast, participants with a more independent self-construal experience stronger reactance when being self-restricted compared to vicariously-restricted. Study 2 (N = 180) replicates this pattern conceptually with regard to individualistic and collectivistic cultural background groups. Additionally, participants’ behavioral intentions show the same pattern of results. Moreover a mediation analysis demonstrates that cultural differences in behavioral intentions could be explained through people´s self-construal differences. Thus, the present studies provide new insights and show consistent evidence for vicarious reactance depending on participants’ culturally determined self-construal.